Hybrid RSA–SHA-256 Scheme for Enhancing Physical-Layer Security in MIMO-OFDM Systems Using SDR Implementation - M Wisnu Gunawan; I Gede Puja Astawa; Amang Sudarsono (Advances in Technology Innovation, 2026)
This research aims to enhance the physical-layer security (PLS) of multi-input multi-output orthogonal frequency division multiplexing (MIMO-OFDM) wireless communication systems. The proposed method integrates Rivest–Shamir–Adleman (RSA)-based subcarrier index scrambling with secure hash algorithm (SHA)-256 hashing to ensure both confidentiality and integrity without altering the transmitted waveform. The scheme is implemented on a 2×2 Universal Software Radio Peripheral (USRP)-based MIMO-OFDM software-defined radio (SDR) testbed and evaluated using symbol distribution analysis, bit-error-rate (BER) performance, and security assessment. Experimental results indicate that RSA-based scrambling substantially increases symbol randomness while preserving Shannon-consistent BER performance across multiple modulation orders, with minimal penalty in signal-to-noise ratio (SNR). Additionally, security analysis demonstrates that the combination of RSA-2048 and SHA-256 is resistant to Wiener’s attack and the common modulus attack, thereby supporting efficient and secure real-time MIMO-OFDM communication.